Toxic sludge is good for you the public relations industry unspun - Robb, Margo; Alper, Loretta; Jhally, Sut.; Goodman, Amy, 1957-; Media Education Foundation (Northampton, MA : Media Education Foundation, 2003)
Tracks the development of the PR industry from early efforts to win popular American support for World War I to the role of crisis management in controlling the damage to corporate image. The video analyzes the tools public relations professionals use to shift our perceptions including a look at the coordinated PR campaign to slip genetically engineered food past public scrutiny.
Sections: The PR industry; Roots in conflict; Not local, not news; Third party advocacy; Selling wars; Controlling damage & managing crisis; Silencing debate -- Extra features: Public relations vs. journalism; More on video news releases; More on genetically modified food; Co-opting movements; Astroturf; Perception management; Democracy in a PR world.
Originally produced in 2002.
Camera, Kelly Garner; editor, Jeremy Smith ; production manager, Kelly Garner.
Narrated by Amy Goodman.
DVD.
Soundtrack in English with subtitles in English or Spanish.
Keywords: Corporations -- Public relations -- United States; Industrial publicity -- Corrupt practices -- United States; Corporations -- Corrupt practices -- United States; Public relations firms -- Corrupt practices -- United States